2012
DOI: 10.2217/pmt.12.78
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Myofascial Pain

Abstract: SUMMARY The objective of this article was to perform a narrative review regarding the treatment of myofascial pain syndrome and to provide clinicians with treatment recommendations. This paper reviews the efficacy of various myofascial pain syndrome treatment modalities, including pharmacological therapy, injection-based therapies and physical therapy interventions. Outcomes evaluated included pain (visual analog scale), pain pressure threshold and range of motion. The evidence found significant benefit with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…At each session, ~30 min is dedicated to these manual techniques to increase flexibility, decrease TrP-related pain and tension, and increase balance and stability. Other pain management strategies, including general and specific respiratory and relaxation exercises, aim to enhance patient’s self-management and self-empowerment skills [ 11 , 42 ]. Aredo et al reported: “this dual approach addresses physiological and psychological components of chronic myofascial pain, alleviates MTrP-related pain, and furnishes patients with coping strategies to redirect their focus during a painful episode” [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…At each session, ~30 min is dedicated to these manual techniques to increase flexibility, decrease TrP-related pain and tension, and increase balance and stability. Other pain management strategies, including general and specific respiratory and relaxation exercises, aim to enhance patient’s self-management and self-empowerment skills [ 11 , 42 ]. Aredo et al reported: “this dual approach addresses physiological and psychological components of chronic myofascial pain, alleviates MTrP-related pain, and furnishes patients with coping strategies to redirect their focus during a painful episode” [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to conduct further studies with a larger number of patients so that analyses can examine different subgroups of patients and determine if the interventions might help to treat underlying pathologies, including spinal conditions, postural abnormalities, and underlying behavioral issues. Furthermore, it is important to include patients on a waiting list or in a sham treatment placebo group in order to assess the superiority of one intervention over another in this patient population [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TT applications could be a treatment option especially in conditions where a dysfunction in blood flow plays an important role in generation and persistence of pain and dysfunction (i.e., osteoarthrosis, tendinopathies, and myofascial pain syndrome). 1,[3][4][5][15][16][17][18][19][20][21][22] Although tendons are poorly vascularized and tendon nutrition is more reliant on synovial fluid diffusion than vascular perfusion, the role of changed vascularization during healing of tendon healing is still not clear. 23 It remains questionable if TT can affect blood flow in other anatomical structures such as tendons and joint capsules.…”
Section: Discussionmentioning
confidence: 99%